A BIBLIOMETRIC ANALYSIS OF FATWA MANAGEMENT AND SHARIAH GOVERNANCE ACROSS SECTORS AND JURISDICTIONS - Mahiddin, Sulaiman; Abdul Rahman, Noor Naemah; Rosele, Muhammad Ikhlas (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Fatwa management and Shariah governance are foundational components in ensuring compliance with Islamic principles across diverse sectors such as finance, healthcare, and legal administration. These mechanisms provide both religious legitimacy and operational guidance for institutions serving Muslim communities. Despite their growing influence, a systematic understanding of global research trends, collaboration patterns, and thematic focuses in this field has yet to be thoroughly examined. This study fills the gap by conducting a comprehensive bibliometric analysis to map the scholarly landscape of fatwa management and Shariah governance across various jurisdictions and sectors. Utilizing the Scopus database, an initial search yielded 2,144 documents, which were refined to a final dataset of 1,526 peer-reviewed publications spanning from 2015 to 2025. The data cleaning and standardization process was conducted using OpenRefine, while VOSviewer was employed for co-authorship, keyword co-occurrence, as well as citation network visualizations. The analysis reveals a consistent upward trend in publications, peaking in 2024, with Malaysia and Indonesia emerging as dominant contributors. The most cited works focus on the intersection of Shariah compliance, corporate governance, and Islamic finance, while key thematic clusters include maqasid al-shariah, fatwa issuance processes, and regulatory integration. "Shariah compliance" emerged as the most central keyword, indicating its foundational role in interdisciplinary scholarship. Co-authorship patterns highlight Malaysia’s leadership in both productivity and collaborative reach, followed by strong regional contributions from Indonesia, Pakistan, and Saudi Arabia. The study concludes that fatwa and Shariah-related research is evolving from niche jurisprudential inquiry into a dynamic, multidisciplinary field engaging with contemporary governance, ethics, and policy implementation. These findings offer a valuable roadmap for future research and institutional development in Islamic legal and financial studies.